Sosialisasi Pendidikan dan Pemberdayaan Masyarakat Sebagai Upaya Mengurangi Jumlah Anak Tidak Sekolah Di Desa Sukoreno, Kecamatan Kalisat, Kabupaten Jember - Rafi’ Zharfan Maulana; Rafli Raikhan Syah; Ragil Prastyo; Nicholas Bintang Satria Dewa; Nindya Ayu Leonita Perwirani; Nurul Hidayati; Kalvin Edo Wahyudi (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The problem of out of school children remains a serious challenge, especially in rural areas such as Sukoreno Village, Jember Regency. This collaborative KKN program aims to reduce the number of out of school children through educational approaches and community empowerment. The method used is descriptive qualitative with observation, interview, and survey techniques. The program was implemented in the form of study buddies, educational interventions with the Forum Anak Desa (FAD), and socialization to parents through community forums and home visits. The results showed an increase in children's motivation to learn, the growth of parents' awareness of the importance of education, and the formation of social networks between the community, students and village government. The findings reinforce the importance of cross sector collaboration in addressing out of school issues in a sustainable manner.